Characterization of L‐type calcium channel activity in atrioventricular nodal myocytes from rats with streptozotocin‐induced Diabetes mellitus. Issue 11 (24th November 2015) - Yuill, Kathryn H.; Al Kury, Lina T.; Howarth, Frank Christopher
Abstract: Cardiovascular complications are common in patients with Diabetes mellitus (DM). In addition to changes in cardiac muscle inotropy, electrical abnormalities are also commonly observed in these patients. We have previously shown that spontaneous cellular electrical activity is altered in atrioventricular nodal (AVN) myocytes, isolated from the streptozotocin (STZ) rat model of type‐1 DM. In this study, utilizing the same model, we have characterized the changes in L‐type calcium channel activity in single AVN myocytes. Ionic currents were recorded from AVN myocytes isolated from the hearts of control rats and from those with STZ‐induced diabetes. Patch‐clamp recordings were used to assess the changes in cellular electrical activity in individual myocytes. Type‐1 DM significantly altered the cellular characteristics of L‐type calcium current. A reduction in peak I CaL density was observed, with no corresponding changes in the activation parameters of the current. L‐type calcium channel current also exhibited faster time‐dependent inactivation in AVN myocytes from diabetic rats. A negative shift in the voltage dependence of inactivation was also evident, and a slowing of restitution parameters. These findings demonstrate that experimentally induced type‐1 DM significantly alters AVN L‐type calcium channel cellular electrophysiology. These changes in ion channel activity may contribute to the abnormalities in cardiac electrical function that are associated with high mortality levels in patients with DM. Abstract : Type‐1 DM significantly altered the cellular characteristics of L‐type calcium current. A reduction in peak ICaL density was observed, with no corresponding changes in the activation parameters of the current. L‐type calcium channel current also exhibited faster time‐dependent inactivation in AVN myocytes from diabetic rats. A negative shift in the voltage dependence of inactivation was also evident, and a slowing of restitution parameters.